Building Blocks Incorporating Waste Materials Bound with Bitumen - Thanaya I.N.A. (Civil Engineering Dimension, 2010)
This paper described an investigation and evaluation which was carried out in the United Kingdom-UK, on the properties of masonry building block materials that incorporate waste materials, namely: steel slag, crushed glass, coal fly ash, rice husk ash (RHA), incinerator sewage sludge ash (ISSA), municipal solid waste incinerator bottom ash (MSWIBA) or shortened as IBA, bound with bitumen or asphalt, named as Bitublock. The binder used was 50 pen bitumen. The properties of the blocks evaluated were: compressive strength, density, porosity, initial rate of suction (IRS), creep, and volume stability. It was found that the Bitublock performance can be improved by optimizing porosity and curing regime. Compaction level of 2 MPa and curing regime of 200°C for 24 hours gave satisfactory bitublock performances that at least comparable to concrete block found in the United Kingdom (UK). The Volume stability (expansion) of the unit is affected by environment relative humidity.